Assessing the appropriateness of paediatric antibiotic overuse in Australian children: a population-based sample survey - Gaston Arnolda; Peter Hibbert; Hsuen P. Ting; Charli Molloy; Louise Wiles; Meagan Warwick; Tom Snelling; Nusrat Homaira; Adam Jaffe; Jeffrey Braithwaite; on behalf of the CareTrack Kids investigative team (BMC, 2020)
Abstract Background Infections caused by antibiotic resistant pathogens are increasing, with antibiotic overuse a key contributing factor. Objective The CareTrack Kids (CTK) team assessed the care of children in Australia aged 0-15 years in 2012 and 2013 to determine the proportion of care in line with clinical practice guidelines (CPGs) for 17 common conditions. This study analyses indicators relating to paediatric antibiotic overuse to identify those which should be prioritised by antimicrobial stewardship and clinical improvement programs. Method A systematic search was undertaken for national and international CPGs relevant to 17 target conditions for Australian paediatric care in 2012-2013. Recommendations were screened and ratified by reviewers. The sampling frame comprised three states containing 60% of the Australian paediatric population (South Australia, New South Wales and Queensland). Multi-stage cluster sampling was used to select general practices, specialist paediatric practices, emergency departments and hospital inpatient services, and medical records within these. Medical records were reviewed by experienced paediatric nurses, trained to assess eligibility for indicator assessment and compliance with indicators. Adherence rates were estimated. Results Ten antibiotic overuse indicators were identified; three for tonsillitis and one each for seven other conditions. A total of 2621 children were assessed. Estimated adherence for indicators ranged from 13.8 to 99.5% while the overall estimate of compliance was 61.9% (95% CI: 47.8-74.7). Conditions with high levels of appropriate avoidance of antibiotics were gastroenteritis and atopic eczema without signs of infection, bronchiolitis and croup. Indicators with less than 50% adherence were asthma exacerbation in children aged > 2 years (47.1%; 95% CI: 33.4-61.1), sore throat with no other signs of tonsillitis (40.9%; 95% CI: 16.9, 68.6), acute otitis media in children aged > 12 months who were mildly unwell (13.8%; 95% CI: 5.1, 28.0), and sore throat and associated cough in children aged < 4 years (14.3%; 95% CI: 9.9, 19.7). Conclusion The results of this study identify four candidate indicators (two for tonsillitis, one for otitis media and one for asthma) for monitoring by antibiotic stewardship and clinical improvement programs in ambulatory and hospital paediatric care, and intervention if needed.